Digital Literacy Competence in Intercultural Interaction in the Dayan Gunung Community, North Lombok, Indonesia - Sutama, I Wayan; Pawito, Pawito; Hastjarjo, Sri; Demartoto, Argyo (Jurnal Communio : Jurnal Jurusan Ilmu Komunikasi, 2025)
This research aims to explains digital literacy competencies based on multicultural and traditional knowledge and their implications for community interaction in Dayan Gunung North Lombok. This research uses a qualitative method with a phenomenological approach. Data were collected through limited observation and interviews. The results show that it is necessary to develop digital literacy and intercultural interaction competencies through (1) understanding and appreciating cultural differences in intercultural interactions, (2) adjusting communication strategies and behaviors to accommodate cultural differences through cultural sensitivity, (3) critically evaluating and analyzing information and media content, (4) collaborating and working together effectively for a common goal, and (5) developing an understanding and practice of digital ethics that promotes inclusivity, equity, and responsible digital citizenship for all multicultural communities. The implication of this study is that to ensure that digitalization brings maximum benefits to traditional communities, a holistic approach is needed, including improved access to technology, digital literacy training, and policies that protect and promote local culture.